STEAM Approach in Continuing Education: Actions to Promote Gender Equality Practices in STEM - Maciano, Giseli Duardo (2023)
This study presents discussions on the importance of promoting interventional actions in the school context, through continuing teacher training involving the STEAM approach, to make the teaching and learning process more attractive and encourage more girls to be interested in STEM areas. For this, a Qualitative Systematic Review was carried out, making it possible to conclude that investing in actions involving the STEAM approach represents a potential for innovating educational practices, as well as supporting the presence of girls in STEM areas.